Peptide fragments of bradykinin show unexpected biological activity not mediated by B1 or B2 receptors. (9th February 2022) - Souza‐Silva, Igor Maciel; de Paula, Cristiane Amorim; Bolais‐Ramos, Lucas; Santos, Anderson Kenedy; da Silva, Filipe Alex; de Oliveira, Vívian Louise Soares; da Rocha, Isabella Domingos; Antunes, Maísa Mota; Cordeiro, Lídia Pereira Barbosa; Teixeira, Vanessa Pereira; Scalzo Júnior, Sérgio Ricardo Aluotto; Raabe, Adriana Campezatto; et al.
Abstract : Background and Purpose: Bradykinin (BK‐(1–9)) is an endogenous nonapeptide involved in multiple physiological and pathological processes. Peptide fragments of bradykinin are believed to be biologically inactive. We have now tested the two major peptide fragments of bradykinin in human and animals. Experimental Approach: BK peptides were quantified by MS in male rats. NO release was quantified from human, mouse and rat cells loaded with DAF‐FM. Rat aortic rings were used to measure vascular reactivity. Changes in BP and HR were measured in conscious male rats. To evaluate pro‐inflammatory effects both vascular permeability and nociception were measured in adult mice. Key Results: BK‐(1–7) and BK‐(1–5) are produced in vivo from BK‐(1–9). Both peptides induced NO production in all cell types tested. However, unlike BK‐(1–9), NO production elicited by BK‐(1–7) or BK‐(1–5) was not inhibited by B1 or B2 receptor antagonists. BK‐(1–7) and BK‐(1–5) induced concentration‐dependent vasorelaxation of aortic rings, without involvement of B1 or B2 receptors. Intravenous or intra‐arterial administration of BK‐(1–7) or BK‐(1–5) induced similar hypotensive response in vivo . Nociceptive responses of BK‐(1–7) and BK‐(1–5) were reduced compared to BK‐(1–9), and no increase in vascular permeability was observed for BK‐(1–9) fragments. Conclusions and Implications: BK‐(1–7) and BK‐(1–5) are endogenous peptides present in plasma. BK‐related peptide fragments show biological activity, not mediated by B1 or B2 receptors. These BK fragments could constitute new, active components of the kallikrein–kinin system.